SPATIAL PRINCIPLES AND ORNAMENTATION ON WATER GARDEN RELICS OF KESULTANAN CIREBON CASE STUDY: WITANA WATER GARDEN, PAKUNGWATI WATER GARDEN, AND SUNYARAGI WATER GARDEN - Andayani (Jurnal Riset Arsitektur, 2019)
Abstract- Water garden is an exterior space of which the main element is water. There is some water garden can be found as a relics of Kesultanan Cirebon. The water gardens in Kesultanan Cirebon are Witana Water Garden, Pakungwati Water Garden, and Sunyaragi Water Garden. Since the era of the Hindusm in Java is already familiar with the concept of a water garden as a sacred bathing place called Petirtaan. But unlike the Hindusm petirtaan, water garden relics of Kesultanan Cirebon has a uniqueness because it is influenced by local and foreign cultures, that can be seen from the concept of spatial principles and ornamentation in water garden. This study aims to conceive the form of macro spatial principles, micro spatial principles, and ornamentation of each water garden. The macro spatial principles include the cosmology of water gardens. The micro spatial principles include petirtaan shapes. This study also examines the cultural factors that affect each water garden and the relationships of those three water gardens.  This research is hopefully may provide insightful development of knowledge especially related to petirtaan. The analytical method that used in this research is using qualitative approach with descriptiveanalytical based on primary and secondary data. Primary data includes direct observation of the object and secondary data includes literature studies on architecture landsape. Ancient water garden located in Cirebon has similarity with the Hindu pentirtaan which serves as a sacred ritual place with uniqueness combined with Islamic water garden of Middle East that serves as a place of recreation. It is also can be seen that there is influence from the Chinese culture on Wadasan ornamentation in each water garden. Therefore, Water garden Cirebon has its own uniqueness because of the acculturation of various existing cultures (Hindusm, Islam, dan Chinese). This shows Cirebon is considered a city that is not closed from outside cultural influences.  Key Words: Water Garden relics of Kesultanan Cirebon, spatial principles and ornamentation, petirtaan